Investigating EFL Teachers' Attitudes Towards the Use of Authentic Materials in Teaching English in Iraqi Kurdistan Region - Fouad Rashid Omar; Husen Fooad Mekael (European Scientific Journal, ESJ, 2020)
Thisstudy investigates Kurdish EFL teachers' attitudestowardsthe use of authentic materials in EFL classroom. To achieve the goals of this study, a questionnaire is used to elicit the required data. The participants of the study consist of 40 EFL teachers (males and females) from different secondary schools in Akre town, Kurdistan Region of Iraq. The findings of the study reveal that Kurdish EFL teachers have a positive attitude towards introducing and applying authentic materials to learners. Moreover, the findings show that the Kurdish EFL teachers' preferences of using authentic materials in their classes do not differ according to their teaching experience. Finally, the findings of the study are discussed and recommendations for further research are provided.